The Effectiveness of Letrozole Adjuvant Therapy - Electro Acupuncture in Reducing the Number of Follicles and Body Weight and Increasing Endometrial Thickness in Women with Polycystic Ovary Syndrome - Wesliaprilius, Todung Antony; Budihastuti, Uki Retno; Melinawati, Eriana; Sulistyowati, Sri; Nurwati, Ida; Hadi, Cahyono (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. Acupuncture can improve menstrual cycle recovery and decrease body mass index (BMI) in women with PCOS. The effect of acupuncture can be enhanced by giving letrozol. Researchers are interested in knowing the comparison between letrozol therapy with letrozol + electroacupuncture on body weight, follicle count, and endometrial thickness in women with polycystic ovary syn